(untitled) (Medico Legal Update, 2020)
Stunting is one of worrying nutritional problems in Indonesia as its prevalence grows every year. The general objective of this study is to determine factors related to stunting. This study used cross-sectional approach conducted in Kendari City and Semarang City from April to December 2019. The population was children under two years old in Kendari City and Semarang City. Data were analyzed quantitatively, consisting of univariate and bivariate analysis with the help of SPSS. Data analyzed were presented in the form of table and description to discuss the results. The results showed that variables that were significantly correlated with stunting in this study were birth weight (p = 0.014), feeding (p = 0.014), mother’s height (p = 0.004), ANC (p = 0.008), mother’s education (p = 0.007), drinking water use (p = 0.0001), toilet use (0.047). To prevent stunting, it is suggested based on this study to focus on variables like feeding suitability, mother’s weight, ANC examination, drinking water use and toilet use.